Low concentrations of a polyphenolic extract from pine bark in high–concentrate diets decrease in vitro rumen ammonia nitrogen but not methane production - Nelson Vera (Taylor & Francis Group, 2021)
This study was conducted to assess the effects of small supplemental doses of a polyphenolic extract from pine bark (PBE) on CH4 output and ruminal fermentation parameters when incubated in batch culture with a high–concentrate diet for 24–h. The data from the dietary substrates supplemented with 0.0, 0.3, 0.6, 0.9, 1.2, 1.5 and 1.8% of PBE were evaluated in a randomized complete block design, and compared using ANOVA followed by Tukey's test and polynomial contrasts. Increasing doses of the PBE caused a linear decrease of the NH3–N concentration (p < 0.001), the potentially degradable dry matter (DM) fraction (p = 0.002), the partitioning factor (p = 0.001), CH4 production and proportion (p = 0.001 and p = 0.029, respectively), although only at 6–h, achieving the lowest productions (p = 0.016) with 1.5 and 1.8% PBE. In contrast, the PBE linearly increased asymptotic gas production (p = 0.007), gas yield (p = 0.004), pH (p = 0.002) and the short–chain fatty acid concentration (p < 0.001) at 24–h. Addition of least 1.5% PBE to high–concentrate diets reduces CH4 production by 31% at 6–h, whereas NH3–N concentration is reduced by 31% at 24–h incubations.